Dimethylaminoparthenolide reduces the incidence of dysplasia and ameliorates a wasting syndrome in HPV16‐transgenic mice. Issue 6 (13th July 2019) - Santos, Joana M. O.; Moreira‐Pais, Alexandra; Neto, Tiago; Peixoto da Silva, Sara; Oliveira, Paula A.; Ferreira, Rita; Mendes, Joaquim; Bastos, Margarida M. S. M.; Lopes, Carlos; Casaca, Fátima; Silva, Sandra; Sweeney, Christopher; et al.
Abstract: The nuclear factor kappa light chain enhancer of activated B cells (NF‐κB) has been implicated in the progression of cancers induced by high‐risk human papillomaviruses (HPV). In cancer patients, NF‐κB is also thought to drive a chronic systemic inflammatory status, leading to cachexia. This study addressed the ability of dimethylaminoparthenolide (DMAPT), a water‐soluble NF‐κB inhibitor, to block the development of HPV‐induced lesions and wasting syndrome in HPV16‐transgenic mice. Mice received DMAPT orally (100 mg/kg/day), once a day, for 6 consecutive weeks. Body weight was monitored weekly along with food and water intake. After 6 weeks the animals were submitted to a grip strength test and sacrificed for specimen collection. Skin samples were analyzed histologically and for expression of NF‐κB‐regulated genes Bcl2 and Bcl2l1 . Gastrocnemius muscles were weighted and analyzed for expression of NF‐κB subunits p50, p52, p65, and Rel‐B. DMAPT reduced the incidence of epidermal dysplasia (18.2% versus 33.3% in HPV16 +/− untreated mice). This was associated with reduced expression of Bcl2 and Bcl2l1 ( p = .0003 and p = .0014, respectively) and reduced neutrophilic infiltration ( p = .0339). Treated mice also showed partially preserved bodyweight and strength, which were independent of the expression levels of NF‐κB subunits in skeletal muscle.These results suggest that NF‐κB inhibition may be a valid strategy against HPV‐induced lesions in vivo and warrant further preclinical tests particularly in the set of combination therapies. In addition, the data may support the use of DMAPT to prevent wasting syndrome.